User-centred iterative design of a smartwatch system supporting spontaneous reminiscence therapy for people living with dementia. (4th June 2022) - Paay, Jeni; Kjeldskov, Jesper; Aaen, Ivan; Bank, Mette
Reminiscence therapy is beneficial for improving the quality of life for older adults living with dementia. However, it is difficult for caregivers in care homes to make this part of their daily practice because remembering a resident's individual stories is difficult. Proximity-aware technologies can make rapid connections between residents, their histories, and nearby artefacts. Through a user-centred iterative design approach, we designed Memento, a prototype technology system that makes it easy and convenient for caregivers to connect residents with real stories from their past and engage them in meaningful conversations. Memento displays connections between a resident's stories and their surroundings on a caregiver smartphone. Caregivers can then subtly use this information to start spontaneous reminiscences with residents, as they go about their everyday activities. Remembering their histories was highly enjoyable for residents, giving them a renewed sense of self-confidence and well-being.